Effectiveness of Sub-Conjunctival Bevacizumab After Pterygium Excision at Armed Forces Institute of Opthalmology - Arsalan, Zahra; Zafar, Omar; Akram, Amjad; Zamir, Quratulain (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the effectiveness of sub-conjunctival Bevacizumab after pterygium excision. Study Design: Quasi-experimental study. Place and Duration of Study: Armed Forces Institute of Ophthalmology Rawalpindi Pakistan, from Aug 2019 to Jan 2020. Methodology: Thirty-six patients were included and divided into two groups. In group A (n=18), pterygium excision with conjunctival auto-graft was followed by injection of 0.3ml of 7.5mg of Bevacizumab. Patients of Group B (n=18) did not receive any Bevacizumab. All the patients were followed up after 7 days, two weeks, 4weeks and 24 weeks after the start of management. The visual analog score was used for pain assessment, Snellen chart for visual acuity and intraocular pressure was measured with applanation tonometry. Results: After six months the recurrence rate was less in Group-A (n=3, 16.6%, p=0.005) than Group-B (n=4, 22.2%, p=0.01) The recurred pterygium size was also greater in Group-B (mean=0.27 ± 0.28mm, p=0.006) than Group-A (mean=0.11 ± 0.21mm, p=0.006). Patients of Group-A experienced less pain post-surgery. The intraocular pressures were same in both the groups. Visual acuity improvement was seen in the Group-A (n=11, 61%, p=0.008)) than group B (n=4.22%, p=0.008). Conclusion: Administration of Bevacizumab under the conjunctiva after pterygium excision may be useful in averting lesion relapse, less post-op pain, and improved visual acuity.